Selected Papers from Coastlab18 Conference - Lara, Javier López; Maza, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents 16 selected papers from the 7th International Conference on The Application of Physical Modelling in Coastal and Port Engineering and Science, Coastlab18. The conference was organized in Santander, Spain, from 22 to 26 May, 2018, by the Instituto de Hidráulica Ambiental de la Universidad de Cantabria, IHCantabria. Coastlab18 welcomed 175 attendees from 18 different countries. The technical program included three renowned keynote lectures and 120 presentations focused on theoretical and practical aspects related to physical modelling in the field of coastal and ocean engineering. Coastal and ocean structures, breakwaters, revetments, laboratory technologies, measurement systems, coastal field measurement and monitoring, combined physical and numerical modelling, physical modelling case studies, tsunamis, and coastal hydrodynamics were the main topics covered in the conference. This book attempts to cover, as completely as possible, all the topics presented during the conference. The papers were accepted after a peer-review process based on their full text.